2014
DOI: 10.1039/c4an00774c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, highly sensitive detection of herpes simplex virus-1 using multiple antigenic peptide-coated superparamagnetic beads

Abstract: A sensitive, rapid, and label free magnetic bead aggregation (MBA) assay has been developed that employs superparamagnetic (SPM) beads to capture, purify, and detect model proteins and the herpes simplex virus (HSV). The MBA assay is based on monitoring the aggregation state of a population of SPM beads using light scattering of individual aggregates. A biotin-streptavidin MBA assay had a femtomolar (fM) level sensitivity for analysis times less than 10 minutes, but the response of the assay becomes nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The study reported a detection limit of 0.8 pM was achieved in a total sample volume of 0.09 mL. Further Ran et al [111] reported a rapid and sensitive, label free magnetic bead aggregation assay for the capture and detection of model proteins of HSV. The biotin streptavidin based magnetic bead assay had the sensitivity in the femtomolar range with an analysis time less than 10 minutes.…”
Section: 4 Studies On Herpes Simplex Virusmentioning
confidence: 99%
“…The study reported a detection limit of 0.8 pM was achieved in a total sample volume of 0.09 mL. Further Ran et al [111] reported a rapid and sensitive, label free magnetic bead aggregation assay for the capture and detection of model proteins of HSV. The biotin streptavidin based magnetic bead assay had the sensitivity in the femtomolar range with an analysis time less than 10 minutes.…”
Section: 4 Studies On Herpes Simplex Virusmentioning
confidence: 99%
“…Nanosized superparamagnetic beads functionalized with specific surface are versatile materials used for various applications in chemical assay, biosensors, bioseparation systems, and biomedical studies (Rampini et al 2015;Rampini et al 2016;Ran et al 2014). To provide specificity, magnet beads can be decorated with ligands, such as antibodies, aptamers, and peptides, qualifying them as useful tools for the purification, detection, and separation of biological analytes from complex samples (Muzard et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Helms et al describe the generation of a multivalent peptide targeting collagen and a subsequent increase in binding affinity of >2 orders of magnitude compared to monovalent formats (Helms et al, 2009). Recently, our lab has described the capture of herpes simplex virus and anticancer proteins from soy whey, using multimeric peptidecoated magnetic particles Ran et al, 2014).…”
Section: Multimeric Peptide Variantsmentioning
confidence: 93%
“…Recently, our lab has described the capture of herpes simplex virus and anticancer proteins from soy whey, using multimeric peptide-coated magnetic particles Ran et al 2014). …”
Section: Multimeric Peptide Variantsmentioning
confidence: 99%